Filter media, methods of making filter media and uses thereof
By using a multi-layer filter medium in the electrified filter, combining conductive activated carbon and porous structure, the problems of high-pressure drop and ozone generation in the prior art are solved, and the filtration effect of efficient particle capture and low-pressure drop is achieved.
Patent Information
- Application Number
- CN202411399738.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-04-29
- Filing Date
- 2017-04-28
- Publication Date
- 2025-01-07
AI Technical Summary
The existing electrified filters have a high voltage drop when filtering submicron particles efficiently, and the charged filters are sensitive to humidity and temperature changes. They produce harmful ozone during the ionization process caused by conventional conductive layers, affecting filtration efficiency.
Using multi-layer filter media, including conductive substrates, insulating substrates and gas adsorption substrates, provides conductivity and gas adsorption through conductive activated carbon in the upstream or downstream layers, ensuring efficient particle capture at low pressure drops and through porous structures Reduce ozone production.
It achieves efficient particle capture at extremely low pressure drop, reduces ozone production, improves filtration efficiency, and is suitable for a variety of air filtration applications.
Smart Images

Figure CN119258657A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a filter medium and its use. In particular, the present invention relates to a filter medium suitable for use in an electrified filter. The present invention also relates to a method for producing the medium and to the use of the medium, in particular for purifying air. Background Art
[0002] There are many known filters for separating particles, such as dust particles, from the air. Both mechanical filters and electrically charged filters (electret) are in use.
[0003] One problem associated with mechanical filters is that in order to achieve high efficiency for sub-micron sized particles, the pressure drop becomes extremely high.
[0004] In a charged air filter, the filtration efficiency is enhanced by introducing a voltage into the filter, whereby the electric field formed guides the charged dust particles into the filter material. A charged filter generally has two conductive metal meshes or plates appropriately arranged on either side of a non-conductive filter, thereby forming a filter assembly. The metal meshes or plates are connected to a voltage source, by which the filter assembly can be charged.
[0005] One problem with electrets is that the charge is sensitive to humidity, temperature changes, and filter contamination. So when you lose charge, you lose efficiency.
[0006] Various improved filter configurations in which conductive plates are integrated into the filter are proposed in the art. JP5067084B2 discloses a filter system comprising an ionization upstream and a filter medium sheet. The filter medium consists of conductive activated carbon on a semi-conductive filter medium sheet.
[0007] WO2007 / 135232A1 discloses a multilayer filter structure having a fibrous isolation layer and two surface layers, the surface layers being formed by a fibrous support matrix treated with a conductive polymer so that it becomes conductive. The fibrous support matrix may be a natural fiber, a glass fiber, or a woven or nonwoven fabric; the fibrous isolation layer is a cellulose layer. WO2007 / 135232A1 teaches that an increase in particle separation efficiency can be achieved by providing an electric charge to particles to be separated from the air using, for example, a corona wire before directing the air flow through the filter material.
[0008] Further technology is represented by US 7,513,933 B2, US 5,403,383 A, US 7,717,986 B2, WO9822222A1, GB 2329598 A and CN 102225281.
[0009] Fibrous support matrices treated with conductive polymers generally cause greater pressure losses during filtration compared to conventional metal meshes or plates.
[0010] A further disadvantage of the filters disclosed in JP 5067084 B2 and WO 2007 / 135232 is that the ionization used to achieve an effective separation of particles from air involves the generation of ozone, which is a harmful gas that needs to be removed from the filtered effluent. Summary of the invention
[0011] It is an object of the present invention to obviate at least some of the problems associated with the present technology and to provide an improved filter media for an electrified filter element suitable for use with an ionization pre-charger.
[0012] In an embodiment, the present technology provides a method for purifying gas by an electrified filtration system, which includes the following steps: providing a gas flow containing suspended particles, especially pollutant particles; pre-charging the particles, especially in the ionization zone; and guiding the gas flow, thereby obtaining a multi-layer filter, whose upstream and downstream layers are continuously charged to enhance the adsorption of particles in the particle receiving layer.
[0013] Typically, the upstream or downstream layer is also grounded.
[0014] The conductivity of the upstream and downstream layers is obtained by providing the filter with a layer of conductive material that is porous enough to allow the passage of air.
[0015] In particular, in the present invention, activated carbon containing a conductive layer is used upstream or downstream or both. The activated carbon provides gas adsorption and electrical conductivity properties.
[0016] According to the invention, therefore, the filter medium comprises in combination a conductive substrate, an insulating substrate and a gas adsorbing substrate which has the property of being conductive and which is electrically separated from the conductive substrate by the insulating substrate.
[0017] More specifically, the filter medium is characterized by what is stated in the characterizing part of claim 1 .
[0018] The method according to the invention is characterized by what is stated in the characterizing part of claim 27 .
[0019] The use according to the invention is characterized by what is stated in claims 30 to 32 .
[0020] Considerable advantages are obtained. Thus, the present material gives extremely high particle capture efficiency at extremely low pressure drop.
[0021] The invention can be used in electrified filters for cabin air filtration in passenger cars and other vehicles. The invention can also be used for HVAC filtration of indoor air, and in portable air purification units and even in vacuum cleaners.
[0022] Next, an exemplary embodiment will be examined in more detail with the aid of the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A cross section of a gas adsorption substrate according to an embodiment of the present invention is schematically shown in side view; Figure 2 shows in schematic side view a cross section of a filter medium including a conductive substrate layer, an insulating layer, and a gas adsorbent substrate layer; Figure 3 The filtration of dust-laden air through an electrified filter of this type is shown in a schematic side view; Figure 4 is a SEM showing particles of activated carbon embedded in a fibrous layer (gas adsorption layer); Figure 5 showing the separation efficiency of the layer comprising activated carbon; and Figure 6 The separation efficiency of a filter medium including three overlapping layers according to one embodiment of the present invention is shown. DETAILED DESCRIPTION
[0024] A number of exemplary and non-limiting embodiments of the invention are described in the accompanying dependent claims.
[0025] The verbs "to comprise" and "to include" are used in this document as open limitations, which neither exclude nor require the presence of unrecited features. Features recited in the dependent claims are freely combinable with each other, unless explicitly stated otherwise. Furthermore, it should be understood that the use of "a" or "an" (i.e. the singular) throughout this document does not exclude a plurality.
[0026] As defined herein, the term "fibrous" means a material consisting primarily of fibers and / or staple fibers.
[0027] In this context, the term "thermoplastic" means a plastic that becomes flexible or moldable above a certain temperature and returns to a solid state when cooled. Exemplary thermoplastic fibers suitable for the present disclosure are polyesters (e.g., polyalkylene terephthalates, such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.), polyalkylenes (e.g., polyethylene, polypropylene, etc.), polyacrylonitrile (PAN), and polyamides (nylons, such as nylon-6, nylon 6,6, nylon-6,12, etc.).
[0028] In this context, the term "substrate" is used to denote a layered structure having one or several layers, which together form the present filter medium. In the following description, the gas adsorbent substrate is also referred to as a "layered structure" to reflect that it comprises several overlapping layers.
[0029] In this context, an "electrified filter" refers to a filter to which a voltage can be directed to enhance filtration. In an electrified filter, an electric field directs the charged dust particles into the filter material. Depending on the actual application and the thickness of the insulation, the voltage between the conductive layers of the filter medium can vary in the range from about 100V to 3kV.
[0030] like Figure 1 As shown in, in one embodiment, a filtering arrangement is provided, which includes a pre-charging unit 8 for ionizing pollutant particles contained in a gas flow upstream (i.e., before a filtering unit), the filtering unit comprising a multi-layer filter medium having substrates 6, 5 and 1-4. The upstream layer 6 and the downstream layers 1-4 are charged successively. The upstream or downstream layer may also be grounded. The conductivity of the upstream and downstream layers is obtained by a conductive material that is sufficiently porous to allow air to pass through.
[0031] The pre-charging unit 8 is usually a corona wire or a similar charger device for producing ionization. Usually, the charger unit 8 is fed with a high voltage. The voltage is, for example, 500V to 10kV.
[0032] In particular, in at least one of the layers, for example in one of the layers 1 - 4 , activated carbon is used, see reference numeral 7 . The activated carbon substrate 1 - 4 is electrically conductive.
[0033] exist Figure 1 In the embodiment of the invention, the activated carbon substrates 1 - 4 are placed downstream, but they may also be placed upstream, with the conductive layer 6 downstream.
[0034] As will be discussed in greater detail, the activated carbon also acts as a gas adsorbing substance and it captures harmful gases and gas components from the gas stream and prevents or at least greatly reduces such emissions from the filter.
[0035] In one embodiment, filter media 1 - 6 are arranged into a conventional filter system, such as by first pleating or folding the media and then placing it into a frame.
[0036] Figure 3 Shown in more detail Figure 1 filter media.
[0037] Figure 3 The conductive layer 6 shown in FIG. 1 generally comprises a matrix formed by a fibrous porous web (e.g., a nonwoven web) that has been impregnated with a conductive component. Typically, the web may have a density of about 10 to 500 g / m 2 Although in order to obtain appropriate porosity and low pressure drop throughout the filter media 1–6, about 10 to 50 g / m 2 , especially about 15 to 30 g / m 2 A grammage of is preferred.
[0038] The fibrous web 6 may comprise fibers selected from polymer fibers and inorganic fibers. The polymer fibers may be natural or synthetic or a combination thereof.
[0039] Examples of natural fibers include cellulose fibers. The cellulose fibers may be selected from the group of natural or regenerated cellulose fibers, such as cellulose, lyocell, viscose, and any other derivative of cellulosic fibers. Chemical wood pulp may also be used as such or in combination with other natural or regenerated cellulose fibers.
[0040] Natural or regenerated natural fibers will thus impart good inherent strength properties. Additional binder fibers (e.g. bicomponent synthetic fibers) may be used in combination, including both natural and synthetic fibers, such as thermoplastic fibers, but natural fibers may thus provide sufficient bonding and inherent strength without the need for added binder fibers.
[0041] The polymeric fibers that may be used in or as a part of the matrix web are typically thermoplastic fibers such as polyester, polyethylene, polyethylene terephthalate, polyolefins, polybutylene terephthalate, and / or polyamides.
[0042] The inorganic fibers are exemplified by glass fibers and glass fiber bundles.
[0043] The matrix comprises, for example, 1 to 99 parts, especially 10 to 90 parts, of natural fibers and 99 to 1 part, especially 90 to 10 parts, of synthetic fibers.
[0044] The porous web is usually made conductive by incorporating a conductive component into it. In one embodiment, the porous web is impregnated with a conductive component to render the web conductive. The conductive component is, for example, conductive ink. The conductive ink may include metal particles, such as silver or copper mixed with a binder. The particles may be granular or formed from finely divided powders or flaky particles. The conductive ink may also include conductive carbon particles, such as carbon black, such as coconut shell carbon black. Carbon black is typically present in the form of a finely divided powder.
[0045] Typically, the conductive ink contains a binder for the conductive component for bonding it to the substrate or the material to be made conductive. The binder may be a thermoplastic or thermosetting material, such as an acrylate, alkylacrylate (methacrylate), epoxy or amine binder. The concentration of the binder is, for example, up to 50 wt%, preferably 1-35 wt%, more preferably 2-25 wt%, based on the total weight of the layer.
[0046] Conductive inks comprising conductive polymers may also be used. Suitable polymers include polyaniline, polypyrrole, polyacetylene, polythiophene and polyparaphenylene and their derivatives and mixtures. A suitable dopant is selected based on the polymer; dodecylbenzensulphonic acid (DBSA) is a commonly used dopant for polyaniline.
[0047] In a preferred embodiment, the conductive layer 6 is formed of a nonwoven matrix impregnated with a non-polymer component, namely carbon black as the conductive component.
[0048] The conductive ink mixed with a binder is applied to the porous material so that the porosity of the fibrous web is substantially maintained. Thus, the coating is applied so that the formation of a continuous film is avoided.
[0049] Typically, the conductive layer exhibits a surface resistivity of less than 1 MOhm / sq or less than 10 10 Volume resistivity in Ohm-cm.
[0050] The thickness of the conductive layer is typically in the range from about 0.01 mm up to 2 mm, in particular about 0.05 to 1 mm, for example 0.1 to 0.5 mm.
[0051] The insulating layer 5 typically comprises fibers, in particular fibers of a natural or synthetic polymer or a combination thereof. Thus, in one embodiment, the insulating layer is produced from cellulose fibers or lignocellulosic fibers. Natural fibers typically provide good insulating properties.
[0052] In one embodiment, the insulating layer is produced from synthetic fibers (e.g. thermoplastic fibers). Examples of suitable thermoplastic materials include polyolefin or especially polyester fibers. It has been found that polyester fibers (e.g. fibers of poly(ethylene terephthalate), PET) will provide electrical insulation in combination with good hydrophobicity and dust holding capacity.
[0053] The layer may be further treated with a water repellent, such as organo-polysiloxane, fluororesin, wax or the like, which enhances the hydrophobicity of the layer.
[0054] The insulating layer is able to hold and bind the particles.The thickness of the layer is typically in the range of from about 0.1 mm up to 5 mm, especially about 0.5 to 4 mm, for example 1 to 3 mm or 1 to 2 mm.
[0055] In one embodiment, the insulating layer has a thickness of 50 to 250 g / m 2 , especially 70 to 200 g / m 2 Weight.
[0056] Typically, the insulating layer exhibits a surface resistivity greater than 10 MOhm / sq or greater than 5x10 10 Volume resistivity in Ohm-cm.
[0057] Figure 2 An embodiment of a gas adsorption layer 1 - 4 is shown in side view.
[0058] exist Figure 2 In the embodiment shown in , the porous gas adsorption layer comprises a combination of three overlapping layers, namely, a first layer 1 with first fibers having a first average diameter; a second layer 2 with second fibers having a second average diameter; and a third layer 3 with third fibers having a third average diameter.
[0059] Typically, at least the majority of the fibers of the three (or more) superimposed layers are independently selected from the group consisting of polymer fibers and inorganic fibers, wherein the polymer fibers are preferably selected from thermoplastic fibers, such as polyester, polyethylene, polyethylene terephthalate, polyolefins, polybutylene terephthalate and / or polyamide, and wherein the inorganic fibers are preferably glass fiber strands. Polymer fibers are particularly preferred.
[0060] The fibers constitute the majority of the weight of the various layers. Thus, in one embodiment, the fibers of the first layer are present in an amount of at least 65 wt%, preferably at least 80 wt%, based on the total fiber weight of the first layer; the fibers of the second layer are present in an amount of at least 65 wt%, preferably at least 80 wt%, based on the total fiber weight of the second layer; and / or the fibers of the third layer are present in an amount of at least 65 wt%, preferably at least 80 wt%, based on the total fiber weight of the third layer.
[0061] The first, second and third fibers may each be the same fiber, or they may be comprised of a mixture of fibers having different average diameters.
[0062] In one embodiment of a multilayer (e.g., 3-layer structure), the second layer 2 between the first layer 1 and the third layer 3 comprises synthetic fibers having an average diameter of less than 10 μm, which are mixed with synthetic fibers having an average diameter greater than 30 μm. It may also comprise fibers having an average diameter in the range of from 10 to 30 μm. For example, the second layer may be formed by a mixture of fibers having an average diameter of 7 μm, 12 μm, and 40 μm. The fiber mixture will provide an increased porosity of the second layer, which is conducive to the incorporation of activated carbon, for example, in granular form (as granules). Fibers having an average diameter in the range of about 40 μm will improve the strength properties of the second layer (i.e., the middle layer).
[0063] Typically, the first layer 1 and the third layer 3 comprise fibers having an average diameter that is smaller than the average diameter of the fibers of the second layer. For example, the first layer and the third layer may be formed from a mixture of fibers having an average diameter of 7 μm and 12 μm.
[0064] In one embodiment, the first layer 1, the second layer 2 and / or the third layer 3 further comprises up to 50 wt%, preferably 2-35 wt%, more preferably 2-25 wt% of a binder fiber, based on the total weight of each of the first layer and / or the third layer. Examples of suitable binder fibers include bicomponent synthetic fibers, such as bicomponent fibers selected from the group consisting of PET-CoPET, PET-CoPE, PE-PET and combinations thereof.
[0065] In one embodiment, the bicomponent fibers present as binder fibers in each layer of the gas adsorbent layer have an average diameter ranging from about 17 μm up to about 30 μm.
[0066] The gas adsorption layered structures 1-4 are porous - just like the conductive layer 6 and the isolation layer 5, and they will allow low pressure drops during filtration. The gas adsorption layers 1-4 exhibit conductivity properties sufficient to enable the gas adsorption layers 1-4 to be used as conductive layers in a filter element in combination with a conductive layer (e.g., conductive layer 6) and an isolation layer (e.g., isolation layer 5), and when they are subjected to a voltage applied to the filter element, they are electrified.
[0067] In the present context, the term "adsorption" will be used to designate the adsorption of substances (eg gases) by the activated carbon, and thus a layer comprising activated carbon will be referred to as an "adsorption" layer.
[0068] In one embodiment, the activated carbon comprises activated carbon powder, in particular a powder formed of particles 7 having an average particle size in the range of 0.1 to 1.5 mm, in particular 0.3 to 1.0 mm.
[0069] In one embodiment, the activated carbon comprises activated carbon fibers or activated carbon in the form of pellets having a diameter of 0.1 to 2 mm, in particular 0.5 to 1.5 mm, and a length of 0.5 to 2 mm.
[0070] In one embodiment, the activated carbon is distributed homogeneously throughout the second layer. "Homogeneously" means that the activated carbon particles, fibers or pellets evenly cover the layer so that a sub-area area unit forming 1 / 10 of the total surface on which the activated carbon is spread contains an amount of carbon proportional to the size of the area ±20%. In other words, a portion of 1 / 10 of the total area contains 1 / 10 ±20% of the total amount of carbon (by weight).
[0071] Typically, the layer 2 comprises activated carbon 7 in an amount sufficient to render the layer electrically conductive. Thus, the loading of activated carbon may be from about 1 to 1000 g / m 2 , especially 10 to 750 g / m 2 , suitably 20 to 500 g / m 2 , such as 50 to 350 g / m 2 .
[0072] Activated carbon usually has a total of more than 500m 2 / g, especially greater than 750m 2 / g, for example 800m 2 / g or more, usually up to 2000m 2 / g large specific surface area.
[0073] The gas adsorption layer will not only provide electrical conductivity, but it will also adsorb gases, such as nitrogen oxides and carbon oxides, and especially ozone. Thus, the gas adsorption layer will prevent harmful ozone generated during the ionization of particles contained in the gas to be filtered from escaping the filter element. This is particularly relevant for the use of the present filter element in applications such as ventilation of buildings and vehicles.
[0074] In one embodiment, the first layer 1 and / or the third layer 3 further comprises up to 50 wt%, preferably 2-35 wt%, more preferably 2-25 wt% of a binder based on the total weight of each of the first layer and / or the third layer. This binder will enhance the mechanical properties of the layer. Typically, the binder may be selected from the group of acrylate, methacrylate, epoxide and amine binders and combinations thereof. Preferably, the second layer is free of a binder (the binder being liquid or solid (hot melt) at room temperature) to avoid loss of specific surface area of the activated carbon which would compromise the gas adsorption properties of the layers 1-4.
[0075] To enhance the conductivity properties, the gas adsorption layer structures 1-4 may be coated with a conductive substance layer 4, as explained above with respect to the conductive layer 6. Thus, a coating comprising a conductive ink may be deposited on the surface of the gas adsorption layer. The conductive ink may comprise metal particles, such as silver or copper mixed with a binder. The particles may be granular, or finely divided powder or flake particles. Furthermore, the conductive ink may contain conductive carbon particles, such as carbon black, such as coconut shell carbon black. Conductive inks comprising conductive polymers may also be used.
[0076] Typically, the conductive ink contains a binder for the conductive component for bonding it to the substrate or the material to be made conductive. The binder may be a thermoplastic or thermosetting material, such as an acrylate, alkylacrylate (methacrylate), epoxy or amine binder. The concentration of the binder is, for example, up to 50 wt%, preferably 1-35 wt%, more preferably 2-25 wt%, based on the total weight of the layer.
[0077] The conductive ink mixed with the binder is applied to the porous material so that the porosity is at least substantially maintained. Thus, the coating 4 is applied so that the formation of a continuous film on top of the gas adsorbing substrate is avoided. To this end, in one embodiment, the conductive ink is applied to the surface of the gas adsorbing substrate in the form of a mixture with a high solids content, and any solvent is evaporated immediately after application.
[0078] In one embodiment, the gas adsorption layer structures 1-4 have a mass of 250 to 500 g / cm 2 , especially 250 to 450 g / cm 2 Weight.
[0079] The gas adsorption substrate is capable of holding and binding particles. The thickness of the substrate is typically in the range of from about 0.1 mm up to 5 mm, especially about 0.5 to 4 mm, for example 1 to 3 mm or 1 to 2 mm.
[0080] Typically, the gas adsorption layer, optionally coated with a conductive layer of the above type, exhibits a surface resistivity of less than 1 MOhm / sq or less than 10 10 Volume resistivity in Ohm-cm.
[0081] The loading amount of the conductive carbon in the form of carbon black in the coating layer 4 of the gas adsorption layer is preferably in the range of 1 to 20 g / m 2 , such as about 5 to 15 g / m 2 within the range.
[0082] It has been found that the filter media described herein have excellent mechanical properties. In particular, according to TAPPI standard T543 (Gurley type tester), the present media shows an extremely high bending stiffness of at least 500 mg obtained from its bending resistance. The media can also be pleated and can maintain its shape during use without significant deformation.
[0083] The media also has a high pore volume within the substrate, which allows for high permeability values. Preferably, the permeability is 0.0447 W / cm2 for 38 cm2 as measured according to ASTM D737. 2 With an area of 1000 m and a pressure of 125 Pa, the air permeability of the media of the present invention is at least 5 cfm.
[0084] In particular, the air permeability of the filter medium is generally 100 to 10,000 l / m 2 s, especially at least 1000 l / m 2 The pressure drop during filtration is less than about 500 Pa, for example less than 400 Pa, especially less than 100 Pa, suitably less than 60 Pa and even less than 45 Pa.
[0085] It has further been found that the filter medium according to the present invention has a filtration efficiency of greater than 80%, in particular greater than 85%, preferably greater than 90% or even greater than 95% relative to 0.4 micron particles at a face velocity of 5.3 cm / s when tested according to the EN 779 test method.
[0086] Surprisingly, the media shows reduced pressure drop over time compared to prior art filter media having similar mechanical properties and particle removal characteristics.
[0087] The process for preparing the gas adsorption substrate (or layered structure) 1-4 preferably comprises the following steps: - providing first, second and third fiber slurries slurried in water as discussed above; - supplying the first slurry to a dewatering screen to form a first sediment; - supplying a second slurry onto the first deposit to form a second deposit on top of the first deposit; - supplying a third slurry onto the second deposit to form a third deposit on top of the second deposit; - removing water from the sediment to form a wet fibrous mat or sheet; and - Drying the wet fibrous mat or sheet while heating to form a substrate.
[0088] In addition to the fibers, the second slurry also comprises activated carbon in the form of granules or fibers, in particular granular activated carbon.
[0089] The synthetic fibers used in the first, second and third layers are preferably man-made fibers having a maximum length.
[0090] In one embodiment, the first slurry comprises water and first fibers, as described above, at least 80% of the fibers being in the form of synthetic fibers, especially man-made fibers, having a diameter in the range from 7 to 12 μm.
[0091] In one embodiment, the second slurry comprises water and second fibers, at least 80% of which are in the form of synthetic fibers, especially man-made fibers, having a diameter in the range from 7 to 40 μm, as described above.
[0092] In one embodiment, the third slurry comprises water and third fibers, as described above, at least 80% of the fibers being in the form of synthetic fibers, especially man-made fibers, having a diameter in the range from 7 to 12 μm.
[0093] In one embodiment of the process, first, second and third homogenous slurries are provided. These slurries can be provided by any method known in the art, such as by adding and mixing fibers in water.
[0094] Once the first, second and third homogenized slurries are prepared, they are applied to a dewatering screen. This screen can be any screen commonly used in papermaking processes. Preferably, this screen is a dewatering endless screen. When the first slurry is supplied to the dewatering screen, a first deposit is formed on the screen. Subsequently, the second slurry is supplied to the first deposit to form a second deposit on top of the first deposit. Then, the third slurry is supplied to the second deposit to form a third deposit on top of the second deposit. The supply of the first, second and third slurries can be performed by using different channels of the headbox of a wet former. Alternatively, a dynamic handsheet former from Techpap SAS (Grenoble, France) can be used to apply slurries one by one. During or after the deposition of the individual slurries, water is removed to form a wet fibrous mat or sheet. Subsequently, the wet fibrous mat or sheet is dried to form a substrate when heated. As defined herein above, this substrate comprises first, second and third layers comprising individual fibers.
[0095] In one embodiment, by applying the first, second and third slurries on top of each other, the boundary region between adjacent layers forms a mixed region comprising the first and second or third and second fibers.
[0096] In such boundary regions, the components of the first and second layers and the components of the third and second layers are intermixed so that there is a fibrous interlocking rather than a clear and defined edge that would separate the individual layers from each other.
[0097] The surface of the filter medium containing activated carbon is optionally coated with a layer of a conductive component to increase the conductivity of the filter medium. This coating can be performed by any conventional coating method, especially by printing or spraying, using a slurry of the conductive component mixed with a binder in a liquid (such as water). By evaporating the liquid from the slurry, a thin layer of the conductive component is placed on the surface of the medium. The amount of binder is limited so that no continuous film is formed on the surface of the gas adsorption layer, but only discrete areas of fibers that bind the conductive component to the first layer are present. Typically, the amount of binder is less than about 40%, especially less than 30%, for example 20 to 5%, of the total weight of the conductive component and the binder. Thus, the porous surface of the material is maintained after deposition of the conductive component.
[0098] As discussed above, in one embodiment, the conductive layer 6 comprises a substrate formed of a fibrous web (e.g., a nonwoven web) that has been impregnated with a conductive component. When a nonwoven web is used as the substrate, it can be produced by a wet-laying or dry-laying process known per se. The web has a density of about 10 to 50 g / m 2 , especially about 15 to 30 g / m 2 Weight.
[0099] In order to impregnate the web with the conductive component, the web is coated from one side, preferably from both sides, with a slurry comprising the conductive component, a binder and a liquid (e.g. water). In order to achieve penetration of the conductive component into the web, the slurry generally comprises equal amounts of the conductive component and the binder in terms of weight - preferably, the amount of binder is greater than 60%, especially greater than 65%, for example 70 to 85%, of the total weight of the conductive component and the binder. The conductive component is impregnated into the matrix in an amount of 10 to 50%, especially 20 to 40%, of the total weight of the conductive layer.
[0100] As discussed above, the insulating layer 3 comprises a fibrous layer comprising or consisting of a composite of natural or recycled fibers, preferably synthetic fibers that have been formed into a nonwoven layer, for example by wet-laid or dry-laid lamination techniques, optionally by using hydroentanglement or needle-punching.
[0101] The three layers 1-4, 5 and 6 are combined into a filter medium by layering so that the layers are mechanically bonded to each other by means of the natural adhesion of the fibers. Preferably, substantially no adhesive is used in the interface between the layers so as not to compromise the porosity of the layered medium.
[0102] The layered medium may be pleated in a manner known per se.
[0103] The filter medium of the present invention is preferably used in such a way that the fluid to be filtered leaves the filter medium at the side of the substrate on which the fine fiber layer is distributed.
[0104] Example: Material: The filter media tested was formed from a combination of a conductive layer, an insulating layer, and a gas adsorbent layer, with a coating on top of the gas adsorbent layer. The material layers were mechanically joined together by placing the layers in an overlapping relationship, while avoiding the use of adhesives that might otherwise compromise porosity and increase pressure drop. The three layered structure was pleated to form a filter element.
[0105] The conductive layer has a thickness of about 37 g / m 2The nonwoven sheet is made of a mixture of natural and regenerated cellulose fibers (cellulose, chemical wood pulp and viscose fibers) mixed with PET fibers. The viscose fibers and PET fibers have an average diameter of about 15 μm. The nonwoven sheet is impregnated with a mixture of 1 part coconut shell carbon black and 3 parts of an acrylate binder to produce a 7.5 g / m 2 The carbon black loading is used to impart conductive properties to the nonwoven sheet.
[0106] The insulation layer is a uniform layer composed of 100% polyester fiber and has a density of 100 g / m 2 Weight.
[0107] The gas adsorption layer is formed of a three-layer nonwoven structure, which includes an intermediate layer formed of a mixture of PET fibers mixed with activated carbon particles between two polymer sheets or layers formed of a mixture of PET fibers. The PET fibers of the intermediate layer have an average diameter of up to 40 μm. The intermediate layer contains 250 g / m2 of PET fibers having an average diameter of 0.3 to 1.0 mm. 2 of carbon particles and exhibits a diameter of about 1000 m 2 / g of surface area. The polymer PET fiber layer comprises fibers having an average diameter of 7 μm and 12 μm. Each of the three layers further comprises bicomponent binder fibers having an average diameter of 17 to 30 μm mixed with the PET fibers, and the polymer PET fiber layer also comprises an acrylate binder. In addition, one surface of the nonwoven structure is provided with a top coating formed of carbon black particles obtained from coconut shells and mixed with an acrylate binder. The carbon black loading is 10 g / m 2 .
[0108] The weight of the gas adsorption substrate is 350g / m 2 .
[0109] The filter medium, formed of three layers on top of each other, is mechanically layered, pleated and placed in a filter frame.
[0110] Nonwoven materials modified with activated carbon are supplied by Ahlstrom of Tampere, Finland under the trade name Trinitex.
[0111] Test method: The filter materials were tested as follows: The test is carried out by applying the principles of the EN779 standard for general ventilation filters. The filter properties measured in the laboratory test are the pressure drop and the partial filter efficiency. The particles are charged with a corona wire charger. The polarity of the corona wire is positive.
[0112] The efficiency was measured in four cases: no voltage connected, only the charger voltage connected, only the collection voltage connected, and both the charger and collection voltage connected. The collection voltage polarity was also positive.
[0113] The filter system is installed and tightly sealed between two chambers in the filter measurement system. In this measurement, the air flow rate is set to 288m 3 / h. The air flow through the filter element is measured by means of a measuring ring, which is calibrated by means of a Venturi tube. The pressure drop is determined by measuring the pressure difference between the upstream and downstream chambers with a micromanometer DPM TT 470S.
[0114] The efficiency is determined by measuring the particle concentration upstream and downstream of the filter element with an optical particle size analyzer PMS LAS-X2 in the particle size range from 0.1 to 2 μm. The test aerosol used is polydisperse DEHS (Di-Ethyl-Hexyl-Sebacate) particles generated with the aid of a Laskin-type aerosol generator.
[0115] The partial filtration efficiency E(dp) is calculated by the following equation: Where C1(dp) is the concentration of the particle size range on the upstream side of the filter element and C2(dp) is the corresponding concentration on the downstream side of the filter element.
[0116] result: The pressure drop was measured with an air flow corresponding to a face velocity of 5.3 cm / s. It was noted that the coating had little effect on the pressure drop. In fact, at a pressure drop of less than 50 Pa, filtration efficiencies of over 90% and even over 95% were achieved for particle sizes in the range of about 0.1 to 2 μm.
[0117] The results also show that conventional metal mesh electrodes can be replaced by a layer of conductive material. In particular, Figure 5 It is shown that conventional electrodes can be replaced by activated carbon nonwovens, ie the gas adsorption layers (reference numerals 1 - 3 ) can be used in this way even without an additional carbon ink coating (reference numeral 4 ).
[0118] The filtration efficiency of these electrode materials is also high. Notably, by utilizing activated carbon as an electrode, a portion of the ozone generated by the particle charger can be removed from the air stream.
[0119] The results of the partial filtration efficiencies of the filter materials (reference numerals 1-6) are shown in Figure 6 middle.
[0120] Reference numerals list 1 nonwoven layer comprising PET fibers 2 Nonwoven layer containing activated carbon particles 3 nonwoven layer containing PET fibers 4 Conductive coating 5 Insulation layer 6 Conductive layer 7 Activated carbon granules 8 Corona wire Reference List Patent Literature JP 5067084 B2 WO2007 / 135232A1 US 7,513,933 B2 US 5,403,383A US 7,717,986 B2 WO 9822222 A1 GB 2329598 A CN 102225281.
Claims
1. A filter medium comprising: - a first conductive fibrous substrate, - a second conductive fibrous substrate spaced apart from said first conductive substrate; as well as - a third insulating substrate provided between the first substrate and the second substrate, for electrically isolating the first conductive substrate from the second conductive substrate, Wherein, the first conductive fibrous substrate comprises: - a first layer having first fibers, said first fibers having a first average diameter; - a second layer having second fibers, said second fibers having a second average diameter; and - a third layer having third fibers, the third fibers having a third average diameter; Wherein, the second layer includes activated carbon in an amount sufficient to render the first fibrous substrate electrically conductive.
2. The filter medium according to claim 1, wherein: The second layer is substantially free of a binder that is liquid at the application temperature.
3. The filter medium according to claim 1 or 2, wherein: The activated carbon comprises activated carbon powder having an average particle size in the range of 0.1 to 1.5 mm, in particular 0.3 to 1.0 mm, and the activated carbon preferably comprises activated carbon fibers or activated carbon pellets.
4. The filter medium according to any one of the preceding claims, wherein: The activated carbon is homogeneously distributed throughout the second layer and / or wherein the activated carbon is capable of adsorbing gaseous components, such as ozone, from an air flow directed through the filter medium.
5. The filter medium according to any one of the preceding claims, wherein: The second layer comprises synthetic fibers having an average diameter of less than 10 μm mixed with synthetic fibers having an average diameter of greater than 30 μm, and / or wherein the first average diameter and the third average diameter are each smaller than the second average diameter.
6. The filter medium according to any one of the preceding claims, wherein: The first layer and optionally the third layer are coated with conductive carbon, in particular mixed with a binder to form a coating, preferably, the first layer and optionally the third layer are coated with a mixture comprising conductive carbon particles, preferably selected from carbon black, mixed with a binder, the mixture being applied to the surface of the first layer, for example by printing or by spraying, to form a coating comprising 1 to 20 g / m 2 of carbon coating.
7. The filter medium according to claim 6, wherein: The first fibers, the second fibers and the third fibers, which are independent of each other, are selected from a group consisting of polymer fibers and inorganic fibers, wherein the polymer fibers are preferably selected from polyester, polyethylene, polyethylene terephthalate, polyolefins, polybutylene terephthalate and / or polyamide, wherein the inorganic fibers are preferably glass fiber bundles, and wherein the first layer, the second layer and the third layer preferably contain bonding fibers, especially bicomponent synthetic fibers selected from the group consisting of PET-CoPET, PET-CoPE, PE-PET and combinations thereof.
8. The filter medium according to any one of the preceding claims, in, The first fibers in the first layer are present in an amount of at least 65 wt%, preferably at least 80 wt%, based on the total fiber weight of the first layer; wherein the second fibers in the second layer are present in an amount of at least 65 wt%, preferably at least 80 wt%, based on the total fiber weight of the second layer; and / or wherein the third fibers in the third layer are present in an amount of at least 65 wt%, preferably at least 80 wt%, based on the total fiber weight of the third layer, and Wherein, based on the total weight of each of the first layer and / or the third layer, the first layer, the second layer and / or the third layer preferably further comprises up to 50wt%, preferably 2-35wt%, more preferably 2-25wt% of binder fiber.
9. The filter medium according to any one of the preceding claims, wherein: Based on the total weight of each of the first layer and / or the third layer, the first layer and / or the third layer further comprises up to 50 wt%, preferably 2-35 wt%, more preferably 2-25 wt% of a binder selected from the group of acrylate, methacrylate, epoxide and amine binders.
10. The filter medium according to any one of the preceding claims, comprising 10 to 750 g / m 2 , especially 20 to 500 g / m 2 , such as 50 to 350 g / m 2 activated carbon, and / or wherein, The filter media has a filtration efficiency of greater than 80%, especially greater than 85%, preferably greater than 90% or even greater than 95% relative to 0.4 micron particles at a face velocity of 5.3 cm / s when tested according to the EN 779 test method.
11. The filter medium according to any one of the preceding claims, wherein: The first conductive substrate or the second conductive substrate or both exhibit a surface resistivity of less than 1 MOhm / sq, and wherein the third substrate preferably has a surface resistivity greater than 10 MOhm / sq and comprises synthetic fibers selected from the group of polymer fibers and inorganic fibers, wherein the polymer fibers are preferably selected from polyester, polyethylene, polyethylene terephthalate, polyolefins, polybutylene terephthalate and / or polyamide, and wherein the inorganic fibers are preferably glass fiber bundles, optionally together with bonding fibers, in particular bicomponent synthetic fibers selected from the group of PET-CoPET, PET-CoPE, PE-PET and combinations thereof.
12. The filter medium according to any one of the preceding claims, wherein: A boundary region between the first layer and the second layer forms a first mixed region including first and second fibers; and a boundary region between the second layer and the third layer forms a second mixed region including second and third fibers.
13. A process for preparing a filter medium according to any one of claims 1 to 12, the process comprising the following steps: - providing first, second and third homogenous slurries; - supplying the first slurry to a dewatering screen to form a first deposit; - supplying the second slurry onto the first deposit to form a second deposit on top of the first deposit; - supplying the third slurry onto the second deposit to form a third deposit on top of the second deposit; - removing water from the deposit to form a wet fibrous mat or sheet; as well as - drying the wet fibrous mat or sheet while heating to form a substrate; in - the first slurry comprises water and first fibers having a first average fiber diameter; - the second slurry comprises water and second fibers having a second average fiber diameter, the second fibers being mixed with activated carbon particles; and - The third slurry comprises water and third fibers having a third average fiber diameter.
14. The process of claim 13, wherein: The second slurry includes second fibers having a second average fiber diameter that is greater than the first average fiber diameter and the third average fiber diameter.
15. A filter element comprising the filter medium according to any one of claims 1 to 12.
16. Use of a filter medium according to any one of claims 1 to 12 or a filter element according to claim 13 in a method for filtering gases, in particular air, using an electrified filter, for example for cabin air filtration in passenger cars or heavy vehicles; or for HVAC filtration of indoor air in a portable air purification unit or in a vacuum cleaner.
Citation Information
Patent Citations
Filter composite with electrostatic and mechanical layers
GB2329598A
JP1975067084A
Air purifying filters and air purifying devices
JP5067084B2
Safe ionizing field electrically enhanced filter and process for safely ionizing a field of an electrically enhanced filter
US5403383A
Electrically enhanced air filtration with improved efficacy
US7513933B2